Natural characteristics in the valley Basin Fouad (Journal of the College of Basic Education, 2024)
Valley Basin Fouad is one of the basins located east of the Western Desert, which is located within Karbala Governorate and slopes northeast of the Razaza Depression. The basin occupies an area of ​​(259.22 km2). The aim of this study is to discover The most important natural characteristics in the Wadi Fouad basin are represented by the geological ground structure, which was studied in the Tertiary period. The region included four rock formations, namely (Al-Nafail, Euphrates, Al-Zahra, and Dammam). The fourth geological period was also studied, and it appears in the study area that there is one deposit, which is (Al-Sabakh). As for the terrain, it has Its height ranged between (32 m) at the downstream area in the northeast of the study area and (250 m) in the southwest of the area. The climate was studied with its elements (solar radiation, temperature, wind, rain, humidity) and the extent of their influence in the Wadi Fouad Basin and a study of water resources. Represented by groundwater, it was found that it is located within a region of high abundance. The types of soils were studied, which were (soils of valley valleys, mixed gypsum desert soils, and saline soils), While natural plants are distinguished by their quality and scarcity, such as perennial plants and annual plants, the study reached a number of conclusions and recommendations that can be exploited by nature and humans.